The role of entrepreneurial leadership in achieving the requirements of knowledge sharing.: An exploratory study of the opinions of a sample of administrative and scientific leaders in the private universities (Norouz and Cihan) in the governorate of Dohuk - Saeed, Abdulazeez; Sultan, Hikmat (Humanities Journal of University of Zakho, 2021)
The current research sought to identify the role of entrepreneurial leadership in achieving the requirements of knowledge sharing by field testing the data of a sample of administrative leaders at the two private universities (Nawroz and Ceyhan) in the city of Dohuk,. To achieve this objective, the researcher built a hypothetical model based on previous literature concerning the subject of the research which is identifying the correlation and impact between the research variables represented by entrepreneurial leadership and the requirements of knowledge sharing. The model consisted of two main hypotheses and a number of and sub hypotheses. A questionnaire form was adopted as a tool collect data and was distributed among administrative leaderships at the two universities A set of statistical methods were used in the analysis besides Statistical Package for Social Sciences (SPSS). The research reached a number of conclusions and set a number of important recommendations.